Chinese Pre-service Music Teachers’ Perceptions of Augmented Reality-Assisted Musical Instrument Learning - Mei, Bing; Yang, Shuxia (Frontiers in Psychology, 2021)
Given the rapid growth of music technology, this study reports Chinese pre-service music teachers’ perceptions of musical instrument learning assisted by augmented reality (AR). In this study, we conducted a small-scale case study with six pre-service teachers enrolled in a music teacher training programme at a comprehensive university in China. Participants engaged in semi-structured, face-to-face interviews after hands-on experiences with an AR-based piano learning app. Thematic analysis revealed that the participants were generally aware of the potential of this instructional approach but doubted its efficacy and exhibited weak intention to adopt it in their future classrooms. Implications of the findings for music teacher training are discussed.